Beyond Symptom Reduction: The Role of Mindfulness-Based Lifestyle Interventions in Cultivating Flourishing and Psychological Capital in Urban Populations - Santos, Luis; Reyes, Maria Clara; Khan, Ali (Research Psychologie, Orientation et Conseil, 2025)
Urban populations often face high levels of stress, anxiety, and burnout, which can negatively affect their overall well-being. While mindfulness-based interventions (MBIs) have been widely studied for their effectiveness in reducing symptoms of mental health disorders, less attention has been paid to their potential in fostering positive psychological outcomes such as flourishing and psychological capital. Flourishing, characterized by life satisfaction, meaning, and engagement, alongside psychological capital, which includes hope, resilience, self-efficacy, and optimism, are essential for long-term well-being and adaptive functioning. This study aims to explore the role of mindfulness-based lifestyle interventions (MBLIs) in cultivating flourishing and psychological capital among urban populations, beyond the reduction of negative symptoms. The research utilized a mixed-methods design, involving pre- and post-assessments using the Flourishing Scale, Psychological Capital Questionnaire, and qualitative interviews. A sample of 100 urban residents participated in an 8-week MBLIs program. Results indicated significant improvements in flourishing (mean increase of 1.2 points) and psychological capital (mean increase of 1.2 points). Participants reported higher levels of self-efficacy, optimism, and emotional resilience. In conclusion, mindfulness-based interventions can serve as a valuable tool in enhancing psychological resilience and well-being, particularly in urban populations, supporting long-term mental health and flourishing.